Associations between lifestyle intervention‐related changes in dietary targets and migraine headaches among women in the Women's Health and Migraine (WHAM) randomized controlled trial - Whitney E. Evans; Hollie A. Raynor; Whitney Howie; Richard B. Lipton; Graham J. Thomas; Rena R. Wing; Jelena Pavlovic; Samantha G. Farris; Dale S. Bond (Wiley, 2020)
Summary Background Migraine and obesity are comorbid particularly in women of reproductive age. Obesity treatment involves reducing energy intake and improving dietary quality but the effect of these changes on migraine is largely unknown. Objective To determine if adherence to dietary intervention targets (ie, total energy, dietary fat intake, and dietary quality) were associated with improvements in migraine and weight. Methods Eighty‐four women with overweight/obesity and migraine were randomized to and completed either a 16‐week behavioral weight loss (BWL) or a migraine education (ME) intervention. For 28 days at baseline and posttreatment, women recorded monthly migraine days, duration, and maximum pain intensity via smartphone‐based diary. At each assessment, weight was measured and dietary intake (total energy intake, percent (%) energy from fat, and diet quality, as measured by the Healthy Eating Index, 2010 [HEI‐2010]) was assessed using three nonconsecutive 24‐hour diet recalls. Results There were no significant group differences in change mean migraine days per month (BWL: ‐2.6+4.0, ME: ‐4.0+4.4; p = 0.1). Participants in BWL significantly reduced their percent fat intake 3.8% (p = 0.004) and improved total diet quality (HEI‐2010) by 6.7 points (p = 0.003) relative to baseline and those in ME (%fat: +0.3%; p = 0.821; HEI‐2010: +0.7; p = 0.725). After controlling for race/ethnicity and weight change, changes in dietary intake were not related to changes in migraine characteristics or weight loss among BWL participants (p's > 0.05). Conclusions Changes in dietary intake among participants were small and may have been insufficient to improve migraine in women with overweight/obesity and migraine.